Os fatores que influenciam o sedentarismo na Terceira Idade - CAMARGO, Fernanda de Aguiar; JESUS, Gabriella Castro Silva de; GUEIROS, Giovanna Schinaider; CONCEIÇÃO, Jéssica Rocha da; ALVES, Laura Conceição; NOVAIS, Tatiane Silva; VELOSO, Yasmin Rosa (107, 2023)
Não fizeram
Keywords: Idosos; Sedentarismo; Ambiente e Saúde